BIOLOGY, HABITS AND LARVAL POLYMORPHISM OF Callopistria floridensis (Guenée) (LEPIDOPTERA: NOCTUIDAE), LARVA DE LOS FERNOS - POSADA-F., FRANCISCO J.; SALDARRIAGA-V., ALFREDO (Revista Colombiana de Entomología, 1985)
Since 1977 the fern moth, Callopristria floridensis (Guenée (Lepidoptera: Noctuidae) has become a serious pest of several ornamental ferns in Colombia. So far 14 fern species have been found as host plants. Records of several years indicate that the insect is more prevalent during dry seasons and occurs in hot temperature climates. C. floridensis besides its economic importance is very notorious because of its larval color polymorphism. This study was conducted in Medellín at an average temperature of 21°C and 75% of relative humidity. This insect has variation in the number of instars, the larval stage can undergo five or six instars. It was found that 92,5% of the total larvae observed, had five instars and from these 54,05% were females a 45,94% males. The remaining 7,5% of the total larvae had six instars and all were females. The life cycle of C. floridensis from egg to adult emergente also varied according to the instar group. The incubation period was 5.71 days for all groups. The five instars male group life cycle was as follows: 36.63 days for larval development including 3.58 days for prepupa; and 18.11 days for the pupa. The total life cycle for this group was 60.45 days. The life cycle of females with five instars was shorter (57.81 days) and is divided as follows: larva 35.95 days including the prepupa (4.0 days) and pupa 16.15 days. The six instar group life cycle was longer (64.04 days). Adults in captivity lived 10.4 days and the sex ratio favored females (1,35 ♀ : 1 ♂) and average oviposition was 465.4 eggs. Five types of color polymorphic larvae were found: 1) totally green larvae; 2) a green larva with a supraspiracular white band and a subspiracular black band; 3) same as anterior but with black dorsal and subdorsal spots; 4) brown to velvet black larva, and 5) same as anterior but with a supraspiracular white band. A given larva can change color during íts development but the color change only occurs after the third instar. Adult sexual dimorphism can be recognized because males are larger, have a filiform antenna but with the first 23 antennal segments broadened, legs are hairy and meta-thorax legs have a tuft of hairs covering two spines in the tibia’ distal ventral part. Females have totally filiform antenna, hairy legs but with a shorter and less abundant tuft of hairs; they also have a darker brown color on the wings.